I have the following equation in Texmaker:

f_{2}(\tau)I_{\theta}(\tau)|_{W_{2}} & = \frac{8\dot{a}c\lambda \e^{2\tau} (\lambda^{2}-\e^{2\tau})}{v_{0}(\e^{2\tau}+\lambda^{3})(\e^{2\tau} + \lambda^{2})}\left(-\frac{2a\lambda (\(\e^{2\tau}+\lambda)}{(\e^{2\tau}+\lambda^{2})(\e^{2\tau}+1)} - \frac{a(\lambda+1)}{(\e^{2\tau}+1)} + \frac{2c\lambda(\lambda^{2}-\e^{2\tau})}{(\e^{2\tau}+\lambda^{2})(\e^{2\tau}+\lambda)}\right) \\
& + \frac{16\dot{b}a c \lambda^{2} \e^{2\tau}}{vb(\e^{2\tau} + \lambda^{3})(\e^{2\tau} + \lambda^{2})} \left( \frac{(\lambda^{2} - \e^{2\tau})(\e^{2\tau} + \lambda)}{(\e^{2\tau} + 1)(\e^{2\tau} + \lambda^{2})} + \frac{(\lambda - \e^{2\tau})}{\e^{2\tau} + 1} + \frac{4c \lambda^{2} \e^{2\tau}}{a(\e^{2\tau} + \lambda)(\e^{2\tau} + \lambda^{2})} \right)

When I compile, I get the error message " LaTeX Error: Bad math environment delimiter." However the PDF file produced is fine.

How do I correct this error? Thanks.

  • 1
    It looks like your code contains a typo, a \( that should probably be a (, in the first line, where it says \left(-\frac{2a\lambda (\(\e^{2\tau}+\lambda)} etc. – GuM May 31 '17 at 0:04

Here is a solution, with multlined from mathtools and fleqn from nccmath (the analog of the fleqn option, but for a single group of equations), combined with geometry, to have sensible outer margins (this supposes you don't use too wide margin notes):


\usepackage{mathtools, nccmath}
\newcommand\e{\mathrm e}


  f_{2}(\tau)I_{\theta}(\tau)\mid{W_{2}} =\\
 \frac{8\dot{a}c\lambda \e^{2\tau} (\lambda^{2}-\e^{2\tau})}{v_{0}(\e^{2\tau}+\lambda^{3})(\e^{2\tau} + \lambda^{2})}%
\left(-\frac{2a\lambda ((\e^{2\tau}+\lambda)}{(\e^{2\tau}+\lambda^{2})(\e^{2\tau}+1)} - \frac{a(\lambda+1)}{(\e^{2\tau}+1)} + \frac{2c\lambda(\lambda^{2}-\e^{2\tau})}{(\e^{2\tau}+\lambda^{2})(\e^{2\tau}+\lambda)}\right) \\%
 + \frac{16\dot{b}a c \lambda^{2} \e^{2\tau}}{vb(\e^{2\tau} + \lambda^{3})(\e^{2\tau} + \lambda^{2})} \left( \frac{(\lambda^{2} - \e^{2\tau})(\e^{2\tau} + \lambda)}{(\e^{2\tau} + 1)(\e^{2\tau} + \lambda^{2})} + \frac{(\lambda - \e^{2\tau})}{\e^{2\tau} + 1} + \frac{4c \lambda^{2} \e^{2\tau}}{a(\e^{2\tau} + \lambda)(\e^{2\tau} + \lambda^{2})} \right) \label{f2Ithetamod}


enter image description here

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.